2021
DOI: 10.1038/s41598-021-02971-z
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning of native T1 mapping radiomics for classification of hypertrophic cardiomyopathy phenotypes

Abstract: We explored whether radiomic features from T1 maps by cardiac magnetic resonance (CMR) could enhance the diagnostic value of T1 mapping in distinguishing health from disease and classifying cardiac disease phenotypes. A total of 149 patients (n = 30 with no heart disease, n = 30 with LVH, n = 61 with hypertrophic cardiomyopathy (HCM) and n = 28 with cardiac amyloidosis) undergoing a CMR scan were included in this study. We extracted a total of 850 radiomic features and explored their value in disease classific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Diffusion tensor parameters were found to be linked to extracellular amyloid deposition assessed by ECV 90 . On the contrary, machine learning showed to add diagnostic value, on top of native T1, for distinction between healthy myocardium, hypertrophic cardiomyopathy and CA 91 …”
Section: Future Directionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Diffusion tensor parameters were found to be linked to extracellular amyloid deposition assessed by ECV 90 . On the contrary, machine learning showed to add diagnostic value, on top of native T1, for distinction between healthy myocardium, hypertrophic cardiomyopathy and CA 91 …”
Section: Future Directionsmentioning
confidence: 91%
“…90 On the contrary, machine learning showed to add diagnostic value, on top of native T1, for distinction between healthy myocardium, hypertrophic cardiomyopathy and CA. 91 diagnosis, Table 2 summarizes the main diagnostic algorithms published in the last few years. 1,7,51,[92][93][94][95][96][97] Overall, they emphasize the importance of clinical red flags, together with laboratory results, ECG, echocardiography and in most cases CMR for the initial screening.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although, this goes beyond current clinical applications of parametric mapping, it may very well lead to significant knowledge discovery in a broad range of cardiac diseases. The first radiomic studies based on T 1 mapping have shown to provide high diagnostic accuracy for the detection of microvascular obstruction (114) and hypertrophic cardiomyopathy phenotypes (115). However, it should be kept in mind that parametric mapping can only be included in radiomic analyses if the mapping techniques are consistent and reproducible in all patients; this may preclude its current use in multi-centric radiomic studies (116).…”
Section: Acquisition and Reconstruction Strategies: Multiparametric M...mentioning
confidence: 99%
“…In the field of cardiological research, radiomics, and radiogenomics can be utilized for the characterization, profiling/phenotyping, and risk stratification of coronary heart disease (CHD), hypertrophic cardiomyopathy, ischemic heart disease, and cerebrovascular disease (70)(71)(72)(73), among others. However, also given its recency, still too much has to be explored in this field.…”
Section: Roles and Applications Of Big Data Generated By Imaging Tech...mentioning
confidence: 99%